Pengaruh Pembelajaran Online Menggunakan Google Classroom Terhadap Peningkatan Hasil Belajar Fisika Siswakelas X SMA Negeri 1 Sayur Matinggi - Mustakim Candra Siagian.; Sri Utami Kholilla Mora Siregar (Universitas Gara Nusantara Padangsidimpuan, 2024)
The problem in this research is that physics material is considered complicated, because it has many formulas that must be memorized, the delivery of material by the teacher only sends assignments without explaining in more detail because learning is only via online. The objectives of this study were: (1) To determine the significant effect of online learning using Google Classroom on the improvement of students' physics learning outcomes during Covid19 Class X SMA Negeri 1 Sayur Matinggi; (2) To determine student responses to the ongoing online learning process.This research is a qualitative descriptive study. The research instruments used were questionnaires and online interviews in google form format. The questionnaire was given to students who were learning online in physics subjects. The results of the study stated that learning using google classroom for students in the midst of the Covid-19 pandemic helped in learning and understanding physics subject matter, while in practicum activities it was felt less effective. The number of students who have used the google classroom application is 6.25% disagree, and 6.25% disagree. The first indicator, as many as 46.875% of students, stated that they did not agree with the ease of accessing the google classroom application. The second indicator was 59.375% of students agreed to understand the learning material using google classroom. The third indicator was 56.25% of students agreed to the effectiveness of using the google classroom application. The fourth indicator was 40.625% of students agreed to use the google classroom application in physics practicum. The lowest score was obtained as much as 40.625% on the indicators of using the google classroom application in physics practicum.